Evaluation of water quality variation in lakes, rivers, and ex-mining ponds in Malaysia (review) - Low, Kah Hin; Koki, I.B.; Juahir, H.; Azid, A.; Behkami, S.; Ikram, R.; Mohammed, H.A.; Zain, Sharifuddin Md (Taylor & Francis, 2016)
Threat posed by the heavy metals has been increasing globally rendering many water bodies unfit for human consumption. This could be due to the increase in concentrations of these metals above natural background. This article reviews the literature data on variation of water quality in rivers, lakes, and ex-mining ponds in Malaysia and other selected countries. World Health Organization (WHO), United States Environmental Protection Agency, and Malaysian water quality standards (INWQS) are used as the baseline for the pollution and health risk assessments. It illustrates that concentrations of Pb, Cd, and As in lakes and ex-mining ponds, and Mn, Cd and Pb in rivers exceed permissible limits for direct consumption. The levels of dissolved oxygen, TSS, and chemical oxygen demand (COD) are not within WHO and INWQS limits, pH of lakes and ex-mining ponds are lower than reference standards while that of rivers are high. Principal component analysis reveals that TSS, COD, BOD, Pb, and As are highly associated with ex-mining ponds. Cluster analysis shows similarity in pollution source between lake and ex-mining ponds. Risk assessment revealed that high chronic daily intake and metal index were beyond acceptable limit indicating high risk and exposure to toxic metals.